Simple control scheme buck-boost DC-DC converter for stand alone PV application system - M. Z. Zulkifli; M. Azri; A. Alias; Md. H. N. Talib; J. M. Lazi (Institute of Advanced Engineering and Science, 2019)
In this paper a buck-boost dc-dc converter for pv application is proposed, which is mainly composed of a buck – boost converter, PV panel, load and a battery. Existing dc-dc converter can convert the power from the PV panel, but unfortunately the PV panel can only provide power when there is a high intensity of light. In order to provide power supply to the load without any interruption, buck-boost dc-dc converter is introduced. The power intermittency issue of PV panel can be overcome with the aid of a secondary supply which is in this case, the batter. The integration system between the primary and the secondary supply is controlled by a simple proposed control scheme. Battery act as a power in the low voltage side while PV panel is taking over in the high voltage side. Buck-boost converter is operated either is buck or boost mode according to the performance of the PV panel. This paper is presented the simple control scheme to decide the mode suitable for the buck and boost mode. Various conditions are simulated to verify the working operation of the buck-boost converter and to representing solar panel in real life. Simulation and experimental are carried out to verify the system.